LUCIFER: a multi-mode NIR instrument for the LBT - Seifert, W; Appenzeller, I; Baumeister, H; Bizenberger, P; Bomans, D; Dettmar, R; Grimm, B; Herbst, T; Hofmann, R; Jutte, M; Laun, W; Lehmitz, M; et al. (2003)
LUCIFER (LBT NIR-Spectroscopic Utility with Camera and Integral-Field Unit for Extragalactic Research) is a NIR spectrograph and imager for the Large Binocular Telescope (LBT) on Mt. Graham, Arizona. It is built by a consortium of five German institutes and will be one of the first light instruments for the LBT. Later, a second copy for the second mirror of the telescope will follow. Both instruments will be mounted at the bent Gregorian foci of the two individual telescope mirrors. The final design of the instrument is presently in progress.LUCIFER will work at cryogenic temperature in the wavelength range from 0.9 mum to 2.5 mum. It is equipped with three exchangeable cameras for imaging and spectroscopy: two of them are optimized for seeing-limited conditions, the third camera for the diffraction-limited case with the LBT adaptive secondary mirror working. The spectral resolution will allow for OH suppression. Up to 33 exchangeable masks will be available for longslit and multi-object spectroscopy (MOS) over the full field of view (FOV). The detector will be a Rockwell HAWAII-2 HgCdTe-array.